The Feasibility of Boat Lift Net in the Archipelagic Fishing Port of Karangantu Banten Province - Epry Rahmawati; Ririn Irnawati; Ani Rahmawati (JURNAL PERIKANAN DAN KELAUTAN, 2017)
This research was conducted in the Archipelagic Fishing Port of Karangantu BantenProvince. It aimed to analyze the feasibility of a boat lift net based on ArchipelagicFishing Port of Karangantu. The research was conducted in November 2015 to January2016. The method used in this study is a survey method. Operation boat lift net inArchipelagic Fishing Port of Karangantu have done by two days fishing (two nights threedays). Based on the results of analysis feasibility (BCR, BEP, and PP) business boat liftnet worth the effort throughout the year (peak season, regular season, and off season).However, from the profits analysis, the revenue during the bad season is lower than thecost incurred. The results of a financial analysis on the operation of the boat lift net intwo seasons are BCR 1.38 (before fuel down) and 1.41 (after fuel down), BEP Rp.198,846,000 (before fuel down) and Rp. 188,090,000 (after fuel down), and PP 1.48 years or 18 months (before fuel down) and 1.38 years or 16 months (before fuel down),payback included in the category of fast because the value of PP < 3 years.